Incidencia de la cartera vencida sobre el patrimonio de las cooperativas de ahorro y credito san francisco y el sagrario en la provincia de Cotopaxi, en el periodo 2015 - Paredes Espín, Daniela Johanna (2017)
The Research Project was carried out in the "El Sagrario y San Francisco savings and Credit Cooperatives”, located in the Cotopaxi Province, which are regulated by the SPES Superintendence of Popular and Solidarity Economy. The main activity of the Cooperative is the raising and placement money according to the balance of its assets in segment 1In 2015, the economic problems began and the sales decreased in a 60%, affecting 25,000 commercial locals due to the activation of the Cotopaxi volcano. It increased the past due loan portfolio. It is for this reason that the purpose of the project was to determine the impact of the overdue portfolio on the assets of the “San Francisco” and “El Sagrario” Savings and Credit Cooperatives through the application of a financial analysis to provide an overview that allowed to incentive collection strategies in the period 2015.The methodology that was applied in the project was quantitative. It was based on the documentary, descriptive and field research to obtain data and necessary financial numbers that were used in the application of financial ratios….